A design of Ti-6Al-4V/ZrB2 multilayers with good thermal stability to enhance mechanical properties of titanium alloy. Issue 5 (1st April 2018) - Nie, Yuyao; Dong, Lei; Wu, Jie; Li, Dejun
Abstract: The inserting a ZrB2 modulation layer into TC4 (Ti-6Al-4V) film to form TC4/ZrB2 multilayers was developed to improve the performance of TC4 film. The enhanced crystallinity of ZrB2 not only enhanced mechanical properties of multilayers with the modulation ratio decreases, but also restricted the propagation of shear bands and promoted the nucleation of new shear bands, which was of help for the plasticity enhancement of TC4 layer. Moreover, the highest hardness (22.54 GPa) and elastic modulus (262.25 GPa) values were reached at l TC4 : l ZrB2 of 1:5, and the law of variation was like that simulated by the rule of mixture. The highest critical fracture load ( L max = 57.6 mN). With the stability of the mixed interface, the multilayers also exhibited excellent thermal stability. High temperature annealing experiments proved that the multilayers maintain good microstructure and the hardness increased about 3 GPa after annealed.